123. Evaluation of gating accuracy for a hybrid MR-guided RT system. (December 2018) - Cusumano, D.; Teodoli, S.; Greco, F.; Boldrini, L.; Cellini, F.; Dinapoli, N.; Chiloiro, G.; Mattiucci, G.; Balducci, M.; Valentini, V.; Azario, L.; De Spirito, M.
Abstract: Purpose: Aim of this study is to dosimetric evaluate the gating accuracy of an MRI-guided radiotherapy system (MRIdian, ViewRay), combining a 0.35 T scanner with 3 Co-60 gamma sources. Methods: An MRI compatible phantom consisting in a piston able to slide inside a cylinder executing a periodic movement was used (CIRS Dynamic Thorax Phantom). An ion chamber (0.125 cc) was inserted inside the piston to perform absolute dose measurement. The extremity of the ion chamber housing is inserted in a 3 × 3 × 2 cm 3 parallelepiped marker that allows its reliable MR visualization. A 3D MR image of the phantom in static position was acquired by using a True Fast Imaging with Steady state Precession (True FISP) sequence. A small target (18 cc) surrounding the ion chamber volume was contoured and a homogeneous dose of 2.16 Gy was prescribed (see Fig. 1). The tracking boundary was obtained expanding the target volume of 5 mm in all directions. The same treatment plan was delivered moving the piston at different speeds (6, 8, 10 mm/s) and for different length path (20, 24, 36, 48 mm). The dose value measured maintaining the piston steady was considered as reference. The gating process was carried out acquiring 4 images/s on a sagittal plan (using a 2D True FISP sequence) and stopping the beam each time the target volume was outside the boundary. Results: Table 1 summarises results obtained. The dose values measured at the different dynamic situations resulted to be very close to the dose reference: in 4 on 5 cases the dose difference resulted less than 0.5%. Even the worst result, obtained when the piston was executing large elongations in short lapses, shows an acceptable value (dose difference equal to 1.58%). Conclusions: The system showed encouraging performances in tracking SBRT target volumes with dose differences always less than 2% at different motion length and speed.